Learning Motivation is Viewed from Goal Orientation, Self-Confidence Control, Test Anxiety and Student Assignment Value - Muhammad Rafli Faishal; Zukhurufurrohmah; Akhsanul In’am (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
This study aims to determine whether there is a significant influence between learning motivation and learning outcomes in mathematics. This study uses a quantitative approach using regression analysis. The population in this study were all grade 9 students at SMPN 11 Pasuruan City, while the sample in this research was 118 grade 9 students. The sampling technique used was random sampling. Learning motivation data was collected through a learning motivation questionnaire, while learning outcomes data was taken from UAS score data at the school. The data was then analyzed using the t test. The results showed that there was a significant influence between learning motivation and students' mathematics learning outcomes.